Molecular recognition thermodynamics of steroids by novel oligo(aminoethylamino)-β-cyclodextrins bearing anthryl : enhanced molecular binding ability by co-inclusion complexation - Liu, Yu (2011)
Three b-cyclodextrin (b-CD) derivatives bearing anthracene group (2–4) were synthesized by the condensation of